Posttranslational modifications of platelet adhesion receptors - Shukun Sun; Bao Qiao; Yu Han; Bailu Wang; Shujian Wei; Yuguo Chen (Elsevier, 2022)
Platelets play a key role in normal hemostasis, whereas pathological platelet adhesion is involved in various cardiovascular events. The underlying cause in cardiovascular events involves plaque rupture leading to subsequent platelet adhesion, activation, release, and eventual thrombosis. Traditional antithrombotic drugs often target the signal transduction process of platelet adhesion receptors by influencing the synthesis of some key molecules, and their effects are limited. Posttranslational modifications (PTMs) of platelet adhesion receptors increase the functional diversity of the receptors and affect platelet physiological and pathological processes. Antithrombotic drugs targeting PTMs of platelet adhesion receptors may represent a new therapeutic idea. In this review, various PTMs, including phosphorylation, glycosylation, ubiquitination, nitrosylation, methylation, lipidation, and proteolysis, of three platelet adhesion receptors, glycoprotein Ib-IX-V (GPIb-IX-V), glycoprotein VI (GPVI), and integrin αIIbβ3, are reviewed. It is important to comprehensively understand the PTMs process of platelet adhesion receptors.